Galaxies: The short wavelength view - Lutz, D; Genzel, R; Sturm, E; Rigopoulou, D; Tran, D; Moorwood, A; Spoon, H; Forster-Schreiber, N; Thornley, M; Alexander, T; Sternberg, A (2000)
With the advent of ISO, mid-infrared spectroscopy has become sensitive enough for detailed analyses of sizeable samples of galaxies. Mid-infrared aromatic emission features are detected strong and ubiquitously in star forming galaxies. They are absent close to an active galactic nucleus but can be strong on larger scales of the AGN host, in particular if there is intense circumnuclear star formation. Through their nebular emission, hot star populations can be studied in dusty environments like starburst galaxies. Starbursts seem to be normal in their hot star initial mass function but short lived due to strong negative feedback. The rich fine structure and coronal line spectrum of active galaxies can be used to reconstruct the otherwise unobservable extreme ultraviolet emission of the AGN. We find evidence for 'big blue bump' emission from the accretion disk but also for neutral absorbers located inside the narrow line region. Mid-infrared emission lines and continuum features provide new diagnostics to discriminate between starburst and AGN activity in obscured galaxies. Using these tools, we find that most ultraluminous infrared galaxies are predominantly starburst powered. Our total sample of about 75 ULIRGs allows to search for trends within the class of ULIRGs: The fraction of AGNs increases with luminosity above similar to 3 x 10(12)L(circle dot) but there is no obvious trend for ULIRGs to be more AGN-like with more advanced merger phase.